Bioinspired design of hybrid composite materials. Issue 1 (2nd January 2019) - Maghsoudi-Ganjeh, Mohammad; Lin, Liqiang; Wang, Xiaodu; Zeng, Xiaowei
ABSTRACT: Mimicking the natural design motifs of structural biological materials is a promising approach to achieve a unique combination of strength and toughness for engineering materials. In this study, we proposed a 2D computational model, which is a two-hierarchy hybrid composite inspired by the ultrastructural features of bone. The model is composed of alternating parallel array of two subunits (A & B) mimicking 'mineralized collagen fibril' and 'extrafibrillar matrix' of bone at ultrastructural level. The subunit-A is formed by short stiff platelets embedded within a soft matrix. The subunit-B consists of randomly distributed stiff grains bonded by a thin layer of tough adhesive phase. To assess the performance of the bioinspired design, a conventional unidirectional long-fiber composite made with the same amount of hard and soft phases was studied. The finite element simulation results indicated that the toughness, strength and elastic modulus of the bioinspired composite was 312%, 83%, and 55% of that of the conventional composite, respectively. The toughness improvement was attributed to the prevalent energy-dissipating damage of adhesive phase in subunit-B and crack-bridging by subunit-A, the two major toughening mechanisms in the model. This study exemplifies some insights into natural design of materials to gain better material performance.